Skulpturen. - Becker, Wolfgang; Brücher, Felicitas Simone; Döring-Mohr, Karin; Gercke, Irmgard; Hunold, Dieter; Legge, Astrid; Ludwig, Peter; Mania, Astrid; Raehs, Andrea; Saum, Jutta; Schödert, Wolfgang; Uelsberg, Gabriele; et al. (Aachen : Ludwig Forum für Internationale Kunst Aachen, 1991)
Ahearn, John ; de Andrea, John ; Antes, Horst ; Balkenhol, Stephan ; Bandau, Joachim ; Bartolani, Judith ; Baselitz, Georg ; Beuys, Joseph ; Boltanski, Christian ; Brüning, Peter ; Bukta, Imre ; Christo ; Cognée, Philippe ; Cox, Stephen ; Dennis, Donna ; Dine, Jim ; Disler, Martin ; Doitschev, Stoju ; Field, Maccles ; Fischli & Weiss ; Fischli, Peter ; Graham, Robert ; Grand, Toni ; Graves, Nancy ; Hanson, Duane ; Heizer, Michael ; Immendorff, Jörg ; Jetelova, Bertram Jesdinsky Magdalena ; Koons, Jeff ; Long, Richard ; Mata, Attila ; Mattheuer, Wolfgang ; Meuser ; Mitljanskij, Daniel ; Müller, Josef Felix ; Nauman, Bruce ; Nestler, Wolfgang ; Oldenburg, Claes ; Opie, Julian ; Orlov, Boris Konstantinovitsch ; Osterwald, Klaus ; Penck, A.R. ; Pitt, Suzan ; Poensgen, Daniel ; Poirier, Anne & Patrick ; Popov, Emil ; Rinke, Klaus ; Roth, Dieter ; Samu, Géza ; Sauermann, Annette ; Schmetz, Klaus ; Segal, George ; Stanev, Angel ; Toya, Shigeo ; Virnich, Thomas ; Warhol, Andy ; Von Wedel, Monika ; Weiss, David ; Wheeler, Doug ; Zilinskaja, Nina
biografie, bibliografie
Skulpturen, Ludwig Forum für Internationale Kunst, Aachen, 1991
Duits
boek